One more reason to learn a new language: Testing academic self-efficacy transfer at junior high school - Luke K. Fryer; W. L. Quint Oga-Baldwin (EARLI, 2017)
The powerful role of self-efficacy within human development broadly, and in education specifically, is widely acknowledged. Less is understood about how self-efficacy might transfer between domains of varying conceptual distance. The current study examines academic self-efficacy in three domains (mathematics, Japanese and foreign language) across students' first year at junior high school. Two studies were conducted each including three school (study-A: n=480; study-B: n=398) to support a test and retest of the differences and inter-relationships across this critical period of adjustment. Difference testing presented a general pattern of significant small declines in students' self-efficacy for all three subjects. Longitudinal latent analyses indicated a consistent moderate effect from foreign language self-efficacy to native language self-efficacy. The pattern of declines, while consistent with research in Western contexts is a source of concern. The transfer of self-efficacy from foreign to native language learning has educational and broad theoretical implications.